Effect of variety and plant spacing on leaf yield of bottle gourd in Bangladesh (Bangladesh Journal of Agricultural Research, 2026)
An experiment was conducted in the farmers’ field at the Farming System Research and Development site of On-Farm Research Division, Bangladesh Agricultural Research Institute, Elenga, Tangail,  during the two consecutive years of Rabi (winter) season of 2014-15 and 2015-16 under young Brahmaputra and Jamuna floodplain to find out the suitable variety and planting spacing of bottle gourd for leaf production purpose through  increasing twig production and ultimately increasing farmers' income in this region of Bangladesh. The experiment was conducted in Randomized Complete Block Design with six dispersed replications. Three varieties viz., BARI Lau-3, BARI Lau-4, and one local variety were tested with four planting spacing viz., 30 cm × 20 cm, 35 cm × 10 cm, 40 cm ×10 cm, and 40 cm × 20 cm. Among the varieties, the highest average twig yield (37.76 t ha-1) and gross margin (Tk. 468170 ha-1) along with BCR (3.69) were obtained from var. BARI Lau-4 along with 30 cm × 20 cm plant spacing. After the completion of a two-years trial, BARI Lau-4 may be recommended for large scale production following 30 cm x 20 cm spacing  for better twig yield and economic benefit. Bangladesh J. Agril. Res. 48(1): 37-45, March 2023